Sejarah Gerakan Sosial Keagamaan di Indonesia melalui Kiprah Muhammadiyah dan Nahdlatul Ulama - Farah Zakia Badriati; Moch Jaka Lelana; Ahmad Daniel Irsyad; Fahri Hidayat (Universitas Veteran Bangun Nusantara, 2025)
This study examines the historical role of Muhammadiyah and Nahdlatul Ulama,the two largest socio-religious organizations in Indonesia, which have significantlyshaped the country’s religious landscape and social development since the earlytwentieth century. Rooted in the social reality that both organizations operatethrough extensive networks of education, religious outreach, and communityservices. This research aims to describe their historical origins, patterns ofmovement, and contributions to the modernization of Islam in Indonesia. Thestudy employs a literature review method by analyzing books, academic journals,organizational documents, and relevant previous studies. A comparativeanalytical approach is used to highlight the similarities and differences in thesocial-religious characteristics of Muhammadiyah and NU. The findings reveal thatMuhammadiyah emerged as a reformist movement focusing on educationalmodernization and purification of Islamic teachings, while NU played a crucial rolein preserving pesantren traditions and local religious culture. Together, they havebecome essential pillars in strengthening Islamic moderation and fostering socialcohesion in Indonesia. This study contributes to Indonesian Islamic historiographyby offering a more comprehensive understanding of the socio-religious dynamicsthat have shaped the distinctive character of Indonesian Islam.